Challenges and opportunities in zoological records and reviews (Zoological Records and Reviews, 2025)
Zoological records and reviews -- the systematic documentation, curation, and synthesis of knowledge about animaldiversity, distribution, ecology, and conservation status -- form the foundational knowledge infrastructure upon which allzoological research, biodiversity assessment, and wildlife management depend. Yet this infrastructure facesunprecedented challenges alongside extraordinary opportunities: the volume of primary zoological literature has grown toover 180,000 publications annually, exceeding human capacity for comprehensive synthesis; taxonomic records remainincomplete for the vast majority of described species; digital transformation has created both powerful new tools forliterature mining, automated synthesis, and open data aggregation, and new risks of data quality degradation, predatorypublishing, and reproducibility failure; and the demands of international biodiversity policy frameworks --Kunming-Montreal GBF, EU Nature Restoration Law, EU Biodiversity Strategy 2030 -- for timely, comprehensive, andpolicy-relevant zoological evidence have never been greater. This review synthesises evidence from 168 primary studies(2010-2025) examining the challenges and opportunities in zoological recording, literature synthesis, open dataprovision, and knowledge translation for European and global biodiversity contexts. We evaluate five majorchallenge-opportunity domains: taxonomic knowledge gaps and digital taxonomy, literature synthesis at scale(systematic reviews and meta-analyses), open data infrastructure and FAIR principles, predatory publishing and researchintegrity, and knowledge translation to policy and practice. A forward-looking framework for transforming Europeanzoological records and review practice in the 2025-2040 period is proposed, aligned with EU open science mandates andinternational biodiversity knowledge infrastructure investments.
Keywords: EU open science; literature synthesis; biodiversity informatics; knowledge translation; predatory publishing; taxonomic knowledge; FAIR principles; open data; systematic review; zoological records